Promoting sustainable food security: integrating mealworms (Tenebrio Molitor) as a nutrient-rich feed source in aquaculture - Nur Efah Arsin; Ching Fui Fui @ Faihana Ching Abdullah; Saleem Mustafa; Abentin Estim (Journal of Hunan University, 2024)
The limited availability and high pricing of fishmeal and fish oil have led to the exploration of sustainable alternatives for aquaculture nutrition. In addition to plants, the use of insects in aquaculture has gained significant attention as an alternative protein to fishmeal, serving as an alternative protein source for both fish and crustaceans. In the last couple of years, mealworm (Tenebrio molitor) larvae have received much attention because of their potential as an alternative protein supplement in aquaculture feed. Mealworms are well known for their high protein levels, well-balanced profile of amino acids (leucine and isoleucine), and good feed efficiency rate. This systematic review highlights the nutritional richness of mealworm meals, highlighting their potential as a protein replacement for fishmeal used in the diets of various farmed fish and crustaceans. Furthermore, this study explored the impact of integrating mealworm meals into the diets of fish and crustaceans by examining aspects such as growth performance, feed utilization, body composition, immune parameters, and antioxidant enzyme parameters. Furthermore, this study investigated various feeding substrates that may have an impact on the growth rate and nutritional composition of mealworm meal, as well as the effects of defatted and full-fat mealworms in the aquaculture feed industry.